Real-time Parameter Estimation for ReconfigurableControl of Unstable Aircraft - Kamali, C.; Pashilkar, A.A.; Raol, J.R. (Defence Science Journal, 2007)
The real-time open-loop parameter estimation of unstable/augmented aircraft is essential forreconfigurable/adaptive control. This paper describes two parameter estimation algorithms basedon the equation-error minimisation principle. One is the recently developed, well-establishedrecursive discrete Fourier transform (DFT) technique in frequency domain. The other is anapplication of recursive least square (RLS) in equation2 error minimisation concept, applied tounstable/augmented aircraft parameter estimation. The RLS technique reported in this paper isimplemented, for the first time, by a methodology that is analogous to the recursive DFT technique.Hence, in time domain, this can be viewed as a counter part of recursive DFT. The algorithmsare implemented and tested for robustness against measurement noise. For the implementation,initially, data was generated under realistic conditions from simulation software that capturesthe dynamics of an unstable high performance aircraft, which is stabilised by full authoritycontrol laws. Subsequently, the algorithms are also tested with real flight data of a highperformance unstable augmented fighter aircraft. The results bring out the merits of the algorithmsand show their suitability for modelling of unstable aircraft, for subsequent adaptive/reconfigurable control or fault diagnosis.